The Impact of Project-Based Flex Blended Learning Model on Critical Thinking Skills of Students in Science Courses - Alfian Erwinsyah; Zohrawaty Hiola; Sabrina Nadjib Mohamad; Dewi Darmiyani Napu; Aljunaid Bakari; Asriyati Nadjamuddin; Rinaldi Datunsolang (Jurnal Penelitian Pendidikan IPA, 2025)
This study aims to analyze the effectiveness of the Project-Based Flex Blended Learning (PjBFBL) model in improving students' critical thinking skills on Ohm's Law material in science courses. The quasi-experimental method uses a Nonequivalent Control Group Design with 41 fourth semester students divided into experimental (PjBFBL) and control (conventional) groups. Instruments include critical thinking tests based on seven indicators (interpretation, analysis, evaluation, inference, explanation, self-regulation, essential questions), analyzed using N-Gain, T-test, and effect size. Results showed the experimental group achieved a moderate N-Gain improvement (0.63) with the highest categories in inference (0.78; high) and explanation (0.73; high), while the control group only had a low N-Gain (0.28). The independent T-test confirmed the significant difference (t (25,092) = 7.230; p<0.05) with an average difference of 35.78% and a large effect size (Cohen's d=2.299). The research conclusion indicates that the PjBFBL model effectively improves critical thinking skills, particularly in multidimensional reasoning and information synthesis, through the integration of authentic projects, hybrid flexibility, and structured collaboration. The findings recommend the adoption of this model in science learning to bridge the 21st century competency gap, noting the need to strengthen the interpretation aspect through more contextualized instruments